O discurso do gestor universitário em campanha - Pires, Karina Coelho (2019)
The main objective of this study is to analyze how discursively constitutes the identity of candidates to the rectory and the potentially ideological meanings present in this practice that can contribute to sustain power relations. For this purpose, we used Fairclough's theoretical line of critical discourse analysis (ACD), which has as its basic theory the influential Systemic functional Linguistics (LSF) with the authors James Martin, Peter White and Michael Alexander Kirkwood Halliday. Our corpus is composed by the transcription of the debate that occurred at the Campus Boa Vista Centro, in the afternoon, among the candidates for the position of rector of IFRR in the campaign of 2016. For the analysis we used the following categories: intertextuality (ational meaning); Interdiscursivity (representational meaning); Modality and evaluativity (identificational meaning). Another important point is the reference to the contribution of the critical theory to the understanding of the ACD, as well as the concept of ideology. We work, in this research, with the concept of John Thompson. To discuss the concept of identity, our social category, we use the authors Manuel Castells, Suart Hall, Kathryn Woodward and Tomaz Tadeu da Silva. The results of our research revealed that candidate Z identified himself as founder (guardian of Local history); Candidate X as part and rejection of power; Candidate Y as excluded from power relations. In this sense, our research identified three different ways of comprehended the power relations exercised at the Federal Institute of Roraima and revealed the IFRR inserted in a larger structure of power, the state of Roraima. The ideological senses pointed to the legitimizing identity, proposed by Castells (2018) that standardizes, does not differentiate and imposes an identity